To find the zeros of the quadratic function \( y = -x^2 + 16x - 39 \), you can set the equation equal to zero and solve for \( x \):
\[ -x^2 + 16x - 39 = 0 \]
To make the calculations easier, you might want to multiply through by -1 to simplify:
\[ x^2 - 16x + 39 = 0 \]
Now, we can use the quadratic formula, which is given by:
\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \]
Here, \( a = 1 \), \( b = -16 \), and \( c = 39 \).
-
Calculate the discriminant \( b^2 - 4ac \): \[ (-16)^2 - 4 \cdot 1 \cdot 39 = 256 - 156 = 100 \]
-
Apply the quadratic formula: \[ x = \frac{-(-16) \pm \sqrt{100}}{2 \cdot 1} = \frac{16 \pm 10}{2} \]
-
Find the two potential solutions: \[ x = \frac{16 + 10}{2} = \frac{26}{2} = 13 \] \[ x = \frac{16 - 10}{2} = \frac{6}{2} = 3 \]
So, the smaller zero is \( x = 3 \) and the greater zero is \( x = 13 \).
Final Answer: smaller zero: \( x = 3 \); greater zero: \( x = 13 \)